Role of tautomerism and solvatochromism in UV–VIS spectra of arylhydrazones of β-diketones - Wojciech, Kuznik; Maximilian, N. Kopylovich; Gunel, I. Amanullayeva; Armando, J.L. Pombeiro; Ali Hussain, Reshak, Prof. Dr.; Kamran, T. Mahmudov; Kityk, Iwan V (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/